The legal system for resolving sports disputes before the Saudi Sports Arbitration Centre (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to provide a deep understanding of the legal system for resolving sports disputes before the Saudi Sports Arbitration Center and to highlight ways to enhance efficiency and transparency in this field. The study adopts an analytical approach based on a comprehensive review of the legal literature on the subject and the analysis of relevant data and information.The study is divided into two main sections: the nature of resolving sports disputes and the legal system for resolving sports disputes in the Kingdom of Saudi Arabia. Each section is further divided into topics and sub-topics according to the nature and requirements of the study.
Keywords: Legal System; Dispute Resolution; Arbitration Center